2020
DOI: 10.3390/cancers12123751
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome in Pediatric Patients with Philadelphia Chromosome Positive ALL Treated with Tyrosine Kinase Inhibitors Plus Chemotherapy—The Experience of a Polish Pediatric Leukemia and Lymphoma Study Group

Abstract: The treatment of children with Philadelphia chromosome positive acute lymphoblastic leukemia (ALL Ph+) is currently unsuccessful. The use of tyrosine kinase inhibitors (TKIs) combined with chemotherapy has modernized ALL Ph+ therapy and appears to improve clinical outcome. We report herein the toxicity events and results of children with ALL Ph+ treated according to the EsPhALL2010 protocol (the European intergroup study of post-induction treatment of Philadelphia chromosome positive ALL) in 15 hemato-oncologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…In Poland, children with the presence of Ph (+) have been treated according to the EsPhALL2010 Protocol since 2012. The estimated 5-year survival rate for children is 74.1% [ 118 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Poland, children with the presence of Ph (+) have been treated according to the EsPhALL2010 Protocol since 2012. The estimated 5-year survival rate for children is 74.1% [ 118 ].…”
Section: Resultsmentioning
confidence: 99%
“…The greatest range of these ailments, in grades from I to III, was observed after imatinib. A patient who received ponatinib developed dermatitis of grade IV [ 118 ].…”
Section: Resultsmentioning
confidence: 99%
“…The authors reported the severity of adverse events of imatinib therapy was mild and mostly Grades 1–2. The most frequently reported forms of toxicity were infections (38.7%), hepatotoxicity (35.5%), and gastrointestinal disorder (22.5%) [ 26 ].…”
Section: Tyrosine Kinase Inhibitorsmentioning
confidence: 99%
“…Identification of the BCR-ABL 1 fusion gene has been associated with a poor prognosis among pediatric patients and, in the pre-tyrosine-kinase inhibitors (TKIs) era, survival was 62% [ 24 ]. Incorporation of the therapy of molecular TKIs significantly improved treatment outcomes [ 25 , 26 ]. However, due to the potential resistance mechanisms and long-term molecular toxicity, further clinical trials concerning TKIs are essential.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, some PK inhibitors, such for Btk, have also been proposed as antithrombotic drugs [ 3 ]. In parallel, the use of a PK inhibitor in acute myeloblastic leukemia (AML) FLT3-ITD or acute lymphoblastic leukemia (ALL) Ph + demonstrates a broad benefit in terms of patient management and toxicity but also reveals new resistance as well as unchanged long-term survival [ 4 , 5 , 6 ].…”
mentioning
confidence: 99%